2007
DOI: 10.1136/jnnp.2006.098244
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up of the first 70 operated adults in the Goteborg Epilepsy Surgery Series with respect to seizures, psychosocial outcome and use of antiepileptic drugs

Abstract: Adult patients who are seizure-free 2 years after resective epilepsy surgery are most likely to still be seizure-free 10 years later. Most are working and have obtained a driving license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
7
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 34 publications
3
39
7
7
Order By: Relevance
“…Successful epilepsy surgery can significantly improve the quality of life of epilepsy patients. Systematic reviews reported that 66%-70% of patients were seizure-free at short-term (,5 y) follow-up (1-4), and 41%-79% were seizurefree at long-term (.5 y) follow-up after temporal lobe resection (5)(6)(7)(8). Successful surgery depends on the accurate localization of epileptogenic focus.…”
mentioning
confidence: 99%
“…Successful epilepsy surgery can significantly improve the quality of life of epilepsy patients. Systematic reviews reported that 66%-70% of patients were seizure-free at short-term (,5 y) follow-up (1-4), and 41%-79% were seizurefree at long-term (.5 y) follow-up after temporal lobe resection (5)(6)(7)(8). Successful surgery depends on the accurate localization of epileptogenic focus.…”
mentioning
confidence: 99%
“…Es existieren jedoch keine ausreichenden Daten, auf deren Grundlage Langzeitauswirkungen des Absetzens einer antikonvulsiven Medikation nach epilepsiechirurgischen Eingriffen beurteilt werden könnten. Mehrere Studien belegen, dass der Anteil von Patienten ohne Medikation nach epilepsiechirurgischen Eingriffen höher ist als in Kontrollgruppen [2,4,12,16,46]. Der Anteil epilepsiechirurgisch "heilbarer" Patienten ist jedoch derzeit unklar.…”
Section: Antikonvulsive Therapie Im Langzeitverlauf Nach Epilepsiechiunclassified
“…Zu berücksichtigen ist, dass allgemeine ökono-mische Aspekte insbesondere in Langzeitbeurteilungen der Beschäftigungsrate einfließen und die Beurteilung mancher Aspekte des Operationeffektes gerade bei langzeitiger Betrachtung erschweren. Eine jüngst publizierte schwedische Studie [2] bestätigte, dass es nur wenigen Patienten durch einen operativen Eingriff gelingt, neu eine Arbeitsstelle zu finden; die Gesamtquote der beschäftigten Patienten sank nach Operation von 74% sogar auf 63% nach zwei Jahren und 55% nach 10 Jahren. Betrachtet man die Patienten separat in Abhängigkeit vom Anfallsoutcome, so behielten anfallsfreie Patienten jedoch meist ihre Arbeit oder wechselten von Teilzeit-auf Vollzeitbeschäftigung, während nicht anfallsfreie Patienten häufig ihren Arbeitsplatz verloren.…”
Section: Psychosoziales Und Neuropsychologisches Outcomeunclassified
See 2 more Smart Citations